Happy England - Huish, Marcus B. (Marcus Bourne), 1845-1921; Allingham, Helen Paterson, 1848-1926 (Salt Lake City, UT : Project Gutenberg, 2017)
"Happy England" by Marcus B. Huish is a biographical-artistic account written in the late 19th century. This work centers around the life and artistic journey of Helen Allingham, a notable figure in the field of watercolour painting, particularly known for her depictions of English landscapes and rural life. The book not only highlights her achievements but also provides insight into the socio-artistic context of women's contributions to art during this period. The opening of the book introduces the theme of the title, emphasizing the joyful and idyllic representation of English life and landscape as seen through Allingham's art. It explains the challenge in selecting a fitting title that encapsulates the essence of the artist's work, which showcases the serene and bucolic beauty of England while avoiding the harsher realities of life. The text also hints at the artist$1 (Bs deep connection to her surroundings, portraying happy and vibrant scenes of rural existence. Through the introduction, readers begin to understand the overall tone of reverence and admiration for Allingham$1 (Bs unique ability to capture the contentment of childhood and the charm of English country life. (This is an automatically generated summary.)s
Our title -- Paintresses, past and present -- The artist's early work -- The artist's Surrey home -- The influence of Witley -- The woods, the lanes, and the fields -- Cottages and homesteads -- Gardens and orchards -- Tennyson's homes -- Mrs Allingham and her contemporaries.
Release date is 2017-05-10
MFR, Adrian Mastronardi, Wayne Hammond and the Online Distributed Proofreading Team
Keywords: Watercolor painting, British; England -- Pictorial works